How do individual differences impact attentional selection ability during volitional control tasks in film? - Simonson, Taylor Leigh (Kansas State University, 2021)
Film viewers’ eye-movements seem largely disconnected from their comprehension; viewers’ eye-movements rarely deviate from narrative elements, regardless of differences in their comprehension (Loschky et al., 2015; Hutson et al., 2017), suggesting bottom-up film features (e.g., color or motion) overwhelm top-down attentional control (e.g., knowledge or experiences). However, viewers’ eye-movements were shown to deviate from narrative elements when given a task at odds with comprehension (Hutson et al., 2017). This suggests viewers used volitional attentional control, which has been suggested to be cognitively demanding during tasks like the anti-saccade task. In such cases, participants tend to make more incorrect, reflexive eye-movements (Mitchell et al., 2002), suggesting difficultly (e.g., cognitive demand) in volitionally controlling their eye-movements. Thus, can people readily use volitional attention during film viewing or is it cognitively demanding for them do so? Furthermore, there have been conflicting results surrounding eye-movement differences across Western and Eastern cultures (Nisbett & Masuda, 2003; Rayner, Castlehano, & Yang, 2007; Goh, Tan, & Park, 2009). Thus, will these cultural differences be evident in our data when using film stimuli, rather than static images, or will bottom-up film features be too overwhelming to show such cultural differences? Finally, studies have shown an important role of working memory capacity in attentional control during cognitively demanding tasks (Unsworth, Schrock, & Engle, 2004; Unsworth & Engle, 2007). Further, these studies have shown differences in performance impact attention control as well. Thus, what role will individual differences (e.g., working memory or task performance) have in attentional selection ability, if any? Participants from Kansas and Japan were eye-tracked while viewing film clips. During film viewing, they were presented with different task goals and levels of attentional demand. Specifically, participants had a primary task of either watching a film clip for comprehension (Comprehension Condition) or drawing a map of the film space from memory (Map Condition). Participants had a secondary task (cognitive load) on half the trials to increase attentional demand. After their working memory capacity was assessed Generally, results showed clearer cultural effects than in past studies using static images, showing that cultural background can overwhelm the otherwise controlling bottom-up features in film. There results also replicated and extended past studies using volitional control measures during film viewing, showing changes in film viewers’ eye-movements depending on the tasks they were given. Importantly, such volitional control of film viewers’ eye-movements came at a cost to film comprehension and was shown to be cognitively demanding. Additionally, there were effects that suggested performance was changing over time on our different performance measures, that working memory played a role in performance, and some evidence to suggest task trade-offs were occurring for Kansas and not Kyoto.
Keywords: Attention; Cultural differences; Eye-movements; Cognitive load